Protective Effects of Pterostilbene on Lipopolysaccharide-Induced Acute Lung Injury in Mice by Inhibiting NF-κB and Activating Nrf2/HO-1 Signaling Pathways - Zhang, Yong; Han, Zhen; Jiang, Aimin; Wu, Di; Li, Shuangqiu; Liu, Ziyi; Wei, Zhengkai; Yang, Zhengtao; Guo, Changming (Frontiers in Pharmacology, 2021)
Pterostilbene (PTER) is a kind of stilbene compound with biological activity isolated from plants such as red sandalwood, blueberry and grape. It has anti-tumor, anti-bacterial, anti-oxidation and other pharmacological activities. However, the underlying mechanism of the protective effect of PTER on lipopolysaccharide (LPS)-induced acute lung injury (ALI) remained not clarified. In this study, LPS was used to establish a mouse model of ALI. Bronchoalveolar lavage fluid (BALF) was collected for inflammatory cells, and the wet-to-dry weight ratio of the lungs was measured. The activities of myeloperoxidase (MPO), antioxidant indexes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and oxidation index such as malondialdehyde (MDA) in lung tissues of mice were measured by the corresponding kits. The levels of Cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), TNF-α, IL-6 and IL-1β in lung tissues of mice were detected by quantitative real-time polymerase chain reaction (qRT-PCR). The activities of Nrf2, HO-1, p-p65 and p-IκB were determined by western blotting. The results showed that the model of LPS-induced ALI was successfully replicated, and it was found that PTER could significantly improve the pathological degree of ALI such as sustained the integrity of the lung tissue structure, alleviated pulmonary interstitial edema and alveolar wall thickening, reduced infiltrated inflammatory cells. PTER could decrease the number of inflammatory cells and obviously inhibit the increase of W/D ratio caused by LPS. PTER could also significantly reduce LPS-induced MPO and MDA, and increase LPS-decreased SOD, CAT and GSH-Px in the lungs. In addition, it was also found that PTER has the ability to decrease LPS-induced production of COX-2, iNOS, TNF-α, IL-6 and IL-1β. The underlying mechanism involved in the protective effect of PTER on ALI were via activating Nrf2 and HO-1, and inhibiting the phosphorylation of p65 and IκB. These results suggested that PTER can protect LPS-induced ALI in mice by inhibiting inflammatory response and oxidative stress, which provided evidence that PTER may be a potential therapeutic candidate for LPS-induced ALI intervention.